2003
DOI: 10.1021/bi034418w
|View full text |Cite
|
Sign up to set email alerts
|

Barley Serine Proteinase Inhibitor 2-Derived Cyclic Peptides as Potent and Selective Inhibitors of Convertases PC1/3 and Furin

Abstract: Proprotein convertases (PCs) are serine proteases containing a subtilisin-like catalytic domain that are involved in the conversion of hormone precursors into their active form. This study aims at designing small cyclic peptides that would specifically inhibit two members of this family of enzymes, namely, the neuroendocrine PC1/3 and the ubiquitously expressed furin. We studied peptide sequences related to the 18-residue loop identified as the active site of the 83 amino acid barley serine protease inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…This finding is consistent with the literature that has shown that conformationally restricted substrates exhibit higher affinity than flexible substrates. [27][28][29] This may indicate that the cyclized ED substrate is a better mimic of the wildtype substrate, or that the natural substrate is conformationally constrained in vivo. Although this is speculation, the practical point in regard to assay design is that the high affinity of the cyclic ED-BACE substrate, together with the high sensitivity of the EFC assay, provides a useful assay format to detect inhibitors using low amounts of enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the literature that has shown that conformationally restricted substrates exhibit higher affinity than flexible substrates. [27][28][29] This may indicate that the cyclized ED substrate is a better mimic of the wildtype substrate, or that the natural substrate is conformationally constrained in vivo. Although this is speculation, the practical point in regard to assay design is that the high affinity of the cyclic ED-BACE substrate, together with the high sensitivity of the EFC assay, provides a useful assay format to detect inhibitors using low amounts of enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous inhibitors as regulators of processing enzymes have been under much investigation (86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96), but few selective inhibitors exist. Specific active-site directed inhibitors of processing enzymes are desirable for mechanistic studies, but such inhibitors are unlikely to provide selective regulation for processing specific proneuropeptide or prohormones, since each protease appears to process multiple proneuropeptide substrates.…”
Section: Inhibitors and Modulators Of Processing Enzymesmentioning
confidence: 99%
“…To date, most reported inhibitors against the proprotein convertase furin have been either proteins (Dahlen et al, 1998;Dufour et al, 2001;Komiyama et al, 2003;Richer et al, 2004) or peptides/peptide derivatives (Cameron et al, 2000a;Villemure et al, 2003;Basak and Lotfipour, 2005). Nonprotein, nonpeptide convertase inhibitors reported thus far are the natural products of the andrographalide family and their succinoyl ester derivatives (Basak et al, 1999); certain metal complexes (Podsiadlo et al, 2004); dicoumarol and its derivatives (Komiyama et al, 2009); and the bicyclic guanidine and pyrrolidine bis-piperazine derivatives we previously identified as PC2 inhibitors (Kowalska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%